IDEOLOGISASI TAFSIR DI KALANGAN ISLAMIS PEREMPUAN BANGLADESH - Muqtada, Muhammad Rikza (Musawa Jurnal Studi Gender dan Islam, 2016)
As an open corpus, al-Qur’an speaks depending on readers. None has authority over al-Qur’an. Consequently, al-Qur’an is often taken by a group of Islamists as a socio-political legitimacy of their movement.Islamist group of Bangladeshi women -BICSa- are ideologizing an interpretation of the Koran which in doctrine to their women cadres to expedite their political missions under Jemaate Islami party (JI) of Bangladesh. BICSa successfully mobilized the women resources as a counterweight to the government by providing an education and a service to the lower levels of society, developing a relationship with the public, and recruiting also mobilizing the political support as the power of women.[Sebagai open corpus, al-Qur’an berbicara tergantung pembacanya. Tidak ada satu pun otoritas yang berkuasa penuh atasnya. Konsekuensinya al-Qur’an sering kali dibawa oleh sekelompok Islamis sebagai bentuk legitimasi gerakan sosial-politis mereka.Sekelompok Islamis perempuan Bangladesh–BICSa– melakukan ideologisasi tafsir al-Qur’an yang diajarkan kepada kader-kader perempuan mereka untuk memperlancar misi politik mereka di bawah partai Jemaate Islami (JI) Bangladesh. BICSa berhasil memobilisasi sumber daya perempuan sebagai penyeimbang pemerintahan dengan menyediakan pendidikan dan jasa bagi masyarakat level bawah, mengembangkan kontak dengan publik, merekrut dan menggalang dukungan politik sebagai kekuatan perempuan]